Minutes (extract)
042-0050-001 Extract from N.C.L. Minutes 21st June 38. (b) Spanish Medical Aid: A letter was reported from the Spanish Medical Aid Committee indicating that the amount raised by the Committe was roughly £54,000, its expenditure had totalled £52,000, and that of the balance more than half was already the subject of commitments. The Committee asked for facilities from the National Council for the issue of an appeal throughout the Movement in aid of its Fund. It was pointed out that the National Council had recently issued a Report of its work for Spanish Relief accompanied by a further appeal for the International Solidarity Fund, and, in the circumstances, it was RESOLVED: "That the request of the Spanish Medical Aid Committee be declined." 292/946/42/50